HYPERCOAGULABILITY IN PATIENTS WITH LUNG CANCER UNDERGOING CHEMOTHERAPY - Mariani Mariani; Herman Hariman; Noni Sari Soeroso (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
There is evidence that in the case of malignancies including lung cancer, that there is hypercoagulability. In spite of this, it is still not clear whether the course of chemotherapy alters the risk. This study aimed to investigate whether there was state of pre-thrombosis and hypercoagulability in patients with lung cancers and the underlying effect of chemotherapy during the treatment. Twelve lung cancer patients were recruited. Their stages and clinical performances were determined. The blood sample was taken before the chemotherapy, shortly after the first- and third-chemotherapy cycles, for the investigation of D-dimer, platelet count, PT (INR), ratios of APTT, and TT. The chemotherapy protocols vary from one patient to the others as well as between the 1st and the 3rd chemotherapy regimens although most of the protocols consist of carboplatin + gemcitabine or carboplatin + paclitaxel. From the thrombosis view of point, they were all asymptomatic and remained so during the period of investigation. Thrombosis is defined as an increase of D-dimer and hypercoagulability as finding one or more of PT (INR), ratio APTT, ratio TT <1.0. The trend of the result in the three sampling points was carried out by ANOVA, while Wilcoxon test for small samples did univariate analysis between two investigations. The result of PT, APTT, and TT indicating hypercoagulability showed that they remained unchanged until the third cycle of chemotherapy (p>0.05). The platelets of patients dropped significantly; median (range) 422 to 287 x 109/L before the chemotherapy to the end of the third cycle respectively. The D-Dimer of patients remained unchanged, however when it was investigated by univariate analysis in the group with D-Dimer >500 ng/mL, this group showed a decreased D-Dimer towards the end of the third cycle (p <0.05). This study demonstrated that there was hypercoagulability in patients with lung cancers before the chemotherapy until the 3rd cycle of chemotherapy. The course of chemotherapy did not alter hypercoagulability. However, in the group where pre-thrombosis had already happen as evidenced by high D-dimer (>500 ng/mL), the chemotherapy showed benefit regarding of reduction of the D-dimer which may lead to the possible breakdown of the existing thrombus.